2018
DOI: 10.3389/fenvs.2017.00096
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants in the Broad-Leaf Mixed Coniferous Forest of Tshothang Chiwog, Bhutan: Floristic Attributes, Vegetation Structure, Ethnobotany, and Socioeconomic Aspects

Abstract: The Himalayan Kingdom of Bhutan, located in one of the global biodiversity hotspots, is endowed with abundant floral wealth, including a wide array of medicinal plants (MPs). However, over-exploitation of these resources is widespread, and only a few studies have assessed the richness and diversity of Bhutanese forests and in particular about the MP resources. A vegetation survey was conducted in Tshothang Chiwog, south-eastern Bhutan to characterize the floristic structure of the broad-leaf mixed coniferous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Drakpa et al [3] prepared a field guide for the Ugyen Wangchuck Institute for Conservation and Environmental Research with 108 species of medicinal plants found in Bumthang Dzongkhag. Jamba & Kumar [11] published a list of 69 species belonging to 69 genera and 41 families from Tshothang Chiwog, Samdrup Jongkhar, Bhutan. The study was part of the first author's M.Sc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drakpa et al [3] prepared a field guide for the Ugyen Wangchuck Institute for Conservation and Environmental Research with 108 species of medicinal plants found in Bumthang Dzongkhag. Jamba & Kumar [11] published a list of 69 species belonging to 69 genera and 41 families from Tshothang Chiwog, Samdrup Jongkhar, Bhutan. The study was part of the first author's M.Sc.…”
Section: Resultsmentioning
confidence: 99%
“…A list of medicinal plants along with their uses was prepared, referring to Lama et al [14]; Wangchuk [24], Wangchuk et al [30], Wangchuk et al [29], Wangchuk et al [26], Lakey & Dorji [13], Wangchuk et al [27], Thomas [21], Wangchuk et al [31], Yeshi et al [36], Chetri et al [2]; Drakpa et al [3], Jamba & Kumar [11], Chetri [1]; FoTM [4,5], Penjor et al [16], Wangchuk et al [32]; Tenzin & Tendar [20], Yangzom et al [33], and Nepal [15].…”
Section: Methodsmentioning
confidence: 99%
“…Ever since the government officially recognized traditional medicines in the country, unsustainable harvesting like poaching and illegal trade of important medicinal plants has taken placed, threatening these plant species [8]. The other common threat includes deforestation, overgrazing, overexploitation, soil erosion, habitat fragmentation, and tourist upsurge [12,6,8,15]. The loss of these plants resources will not only extinct ethno-medical and ethnobotanical practices, but will also affect the health care system and the ecosystem of the nature.…”
Section: Original Research Articlementioning
confidence: 99%
“…Reduces fever arising from poisoning and heals wounds, mumps and body swelling[7,34]. Used in eye diseases, diarrhea, jaundice, skin diseases, syphilis, chronic rheumatism, urinary disorders, diabetes, jaundice, gastrointestinal problem [29,35], malaria fever, in relieving pyrexia, as a wash for ulcer sores, as an eye lotion in conjunctivitis [36,37], allays chronic cough and cold[15,34]. Treatment of abscess, boils, malaria, for treatment of insect, snake and bug bites, edema, laryngitis, sore throats, acute tonsillitis, otitis media, in nose bleeding [40], boils, burns, and itches[11,39].…”
mentioning
confidence: 99%